2002
DOI: 10.1038/emm.2002.34
|View full text |Cite
|
Sign up to set email alerts
|

Sox-4 is a positive regulator of Hep3B and HepG2 cells' apoptosis induced by prostaglandin (PG)A2 and Δ12-PGJ2

Abstract: We reported earlier that expression of Sox-4 was found to be elevated during prostaglandin (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
28
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 16 publications
2
28
1
Order By: Relevance
“…Recently, increasing evidence has shown that SOX4 is highly up-regulated in a number of tumors, including breast cancer (22), lung cancer (24), colon cancer (25), meduloblastoma (26), salivary gland cancer (27), and hepatocellular carcinoma (28). Furthermore, higher SOX4 expression correlates with better survival in bladder tumor patients (29), and it promotes prostaglandina-induced apoptosis in hepatocellular carcinoma (30), suggesting that SOX4 has a potential tumorsuppressive function. However, the precise mechanism by which SOX4 is involved in tumorigenesis remains largely unknown.…”
mentioning
confidence: 99%
“…Recently, increasing evidence has shown that SOX4 is highly up-regulated in a number of tumors, including breast cancer (22), lung cancer (24), colon cancer (25), meduloblastoma (26), salivary gland cancer (27), and hepatocellular carcinoma (28). Furthermore, higher SOX4 expression correlates with better survival in bladder tumor patients (29), and it promotes prostaglandina-induced apoptosis in hepatocellular carcinoma (30), suggesting that SOX4 has a potential tumorsuppressive function. However, the precise mechanism by which SOX4 is involved in tumorigenesis remains largely unknown.…”
mentioning
confidence: 99%
“…12 -PGJ2 especially induces Sox-4 protein and this phenom enon is restricted only to 12 -PGJ2, but not to cisplatin (data not shown). Sox-4 was shown to be overexpressed in HepG2 and Hep3B cells by 12 -PGJ2 and induced apoptosis through activation of caspase 1 (Ahn et al, 2002). Also GRR (Gly rich region) region of Sox-4 was proved to induce apoptosis directly for itself (Eun-Hae Hur, unpublished).…”
Section: Discussionmentioning
confidence: 99%
“…To study the mechanism of 12 -PGJ2-induced apoptosis in Hela Cells, we examined caspase-independent pathway together with bcl-2 effects on caspase cascade. 12 -PGJ2 can exert its ability in many ways; through activation of caspase-1 (Ahn et al, 2002) or induce apoptosis regulators, like Sox-4, which directly plays a role in apoptosis (Hur et al, 2004). In the case of 15-deoxy--12,14-PGJ2(15d-PGJ2), the hydrolysis product of 12 -PGJ2, CHOP gene was transcriptionally activated to induce apoptosis (Shoichi et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of genes and their products, including p53, c-myc, heat shock protein 70, Sox-4 (Sry-HMG box gene) and SSF-1 (a novel splicing factor), are up-and down-regulated by presence of 12 -PGJ2 in human hepatocarcinoma cells. And these genes and their products serve as a positive or negative regulator in 12 -PGJ2-induced apoptotic pathway in tumor cells (Lee et al, 1995;Ahn et al, 1998;Ahn et al, 1999;Ahn et al, 2002). But the precise mechanism by which 12 -PGJ2-initiates the cellular events resulting in cell death is not fully understood.…”
Section: Introductionmentioning
confidence: 99%